2000
DOI: 10.1063/1.1318365
|View full text |Cite
|
Sign up to set email alerts
|

Response to “Comment on ‘Quantum-confinement effects on the optical and dielectric properties for mesocrystals of BaTiO3 and SrBi2Ta2O9’ ” [J. Appl. Phys. 88, 6092 (2000)]

Abstract: In this reply, the authors show that the argument by Scott regarding the band gap of bulk SrBi2Ta2O9 (SBT) is not based on concrete evidence. The authors will also show additional data from a Raman study of a powdered SBT sample to prove that the surface of the specimen was not covered by Bi2O3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…We have reported that the maximum temperature in the real part of temperature-dependent complex dielectric constants T m (Ј) of BaTiO 3 ͑BTO͒, SrBa 2 Ta 2 O 9 ͑SBTO͒, and LiTaO 3 ͑LTO͒ nanoparticles embedded in amorphous SiO 2 were 60, 180, and 365°C, respectively, at the applied field frequency ͑f ͒ of 100 kHz. [7][8][9][10] The ferroelectric-paraelectric transition temperatures T c (Ј) of the bulk BTO, SBTO, and LTO, powders were 130, 310, and 645°C, respectively. For BTO, SBTO, LTO, the T m values were lower than the T c values by 70, 130, and 280°C, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have reported that the maximum temperature in the real part of temperature-dependent complex dielectric constants T m (Ј) of BaTiO 3 ͑BTO͒, SrBa 2 Ta 2 O 9 ͑SBTO͒, and LiTaO 3 ͑LTO͒ nanoparticles embedded in amorphous SiO 2 were 60, 180, and 365°C, respectively, at the applied field frequency ͑f ͒ of 100 kHz. [7][8][9][10] The ferroelectric-paraelectric transition temperatures T c (Ј) of the bulk BTO, SBTO, and LTO, powders were 130, 310, and 645°C, respectively. For BTO, SBTO, LTO, the T m values were lower than the T c values by 70, 130, and 280°C, respectively.…”
mentioning
confidence: 99%
“…The dipole moment of each nanoparticle disappears at T c and the system reaches intrinsic paraelectric state. [7][8][9][10] In diluted systems of ferroelectric nanoparticles, the local ordering is due to electric dipoles. The spin representing a magnetic moment of magnetic spin glasses turns into a pseudospin representing the electric moment of dipolar glasses.…”
mentioning
confidence: 99%